2015
DOI: 10.1007/s40243-015-0042-0
|View full text |Cite
|
Sign up to set email alerts
|

Copper nanoparticles stabilized by reduced graphene oxide for CO2 reduction reaction

Abstract: Carbon dioxide (CO 2 ) is one of the main gases produced by human activity and is responsible for the green house effect. Numerous routes for CO 2 capture and reduction are currently under investigation. Another approach to mitigate the CO 2 content in the atmosphere is to convert it into useful species such as hydrocarbon molecules that can be used for fuel. In this view, copper is one of the most interesting catalyst materials for CO 2 reduction due to its remarkable ability to generate hydrocarbon fuels. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 52 publications
(65 reference statements)
4
39
0
Order By: Relevance
“…As a result, electron transfer to adsorbed CO 2 molecules (RDS) was improved which in turn improves the CO 2 RR kinetics. A similar result was observed for Cu NPs on reduced graphene oxide (rGO) supports, [67] in which the presence of surface functional groups stabilises the NPs by decreasing the interfacial energy between the Cu and rGO. [28] …”
Section: Graphene Supported Nanoparticlessupporting
confidence: 66%
“…As a result, electron transfer to adsorbed CO 2 molecules (RDS) was improved which in turn improves the CO 2 RR kinetics. A similar result was observed for Cu NPs on reduced graphene oxide (rGO) supports, [67] in which the presence of surface functional groups stabilises the NPs by decreasing the interfacial energy between the Cu and rGO. [28] …”
Section: Graphene Supported Nanoparticlessupporting
confidence: 66%
“…In this context, it is still necessary to develop catalysts with onset potential and current densities optimized for CO 2 RR. The electrode stability is another aspect of fundamental importance in electrocatalysis, since it is necessary that the catalysts exhibit high stability to be applied in several cycles or for long operation times ,,. Researchers have observed that despite bulk Cu electrodes are capable of reducing CO 2 electrochemically in aqueous solution, their stability is insufficient for practical use .…”
Section: Introductionmentioning
confidence: 99%
“…The electrode stability is another aspect of fundamental importance in electrocatalysis, since it is necessary that the catalysts exhibit high stability to be applied in several cycles or for long operation times ,,. Researchers have observed that despite bulk Cu electrodes are capable of reducing CO 2 electrochemically in aqueous solution, their stability is insufficient for practical use . In this sense, the low electrochemical stability of Cu electrodes must be overcome for practical purposes as catalysts for CO 2 reduction .…”
Section: Introductionmentioning
confidence: 99%
“…These could be ascribed to the synergistic effect of hydrogen bonding between CuNCs and rGO [19,20]. Also, contrast found in FTIR spectrum at 860 cm −1 and 1400 cm −1 correspond to deformation of Cu-O-H, stretching of C-O epoxide, and other peaks before and after rGO-CuNCs preparation which reveals that CuNCs were decorated on rGO [21]. These observations demonstrate that the molecules in rGO facilitate coordination with CuNPs species.…”
Section: Resultsmentioning
confidence: 76%